Arthritis, Depression, and Falls Among Community-Dwelling Older Adults: Evidence From the Health and Retirement Study. (September 2018) - Quach, Lien T.; Burr, Jeffrey A.
The aims of this study were to examine the association between different types of arthritis and falls and to investigate whether clinically significant depression symptoms (CSDS) moderate these relationships. The study used nationally representative data from the 2008 Health and Retirement Study ( n = 7, 715, M age = 75, 62% female, and 90% White). Among the respondents, 42% experienced at least one fall during the previous 2 years. About one third had some form of arthritis: 22% osteoarthritis (OA), 4.8% rheumatoid arthritis (RA), 2.3% both OA and RA, and 7.9% with other arthritis types. About one fifth of respondents had CSDS. OA and CSDS are associated with the odds of falling (17% and 29%, respectively), adjusting for socio-demographic characteristics, lifestyle, health conditions, and psychiatric medications. There was no statistically significant interaction between types of arthritis and CSDS. Health care providers should pay attention to managing arthritis, especially OA, and CSDS to prevent falls among older adults.